Economic barriers and their impact on access to healthcare facilities - Neugebauer, Jan; Lovětínská, Ivana; Vokoun, Marek; Rotschedl, Jiří (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Healthcare access is very standard nowadays. Healthy people generally do not prioritize how they access healthcare facilities. However, the most common client of a healthcare facility is not a healthy person, but one who is suffering. In this case, many limitations can impact access to proper care. The study’s primary objective was to identify all potential economic barriers that affect access to healthcare facilities. We established the theoretical basis using the PRISMA-PICOT approach, then focused on the qualitative approach, using semi-structured interviews to test our theories. Results show that a few spectrums of people are in different conditions, making them vulnerable. Based on the group's vulnerability and specific needs, there are various economic barriers, ranging from low income to inadequate travel approaches. For example, people from rural areas often have limited transportation options, and many are unable to use their mobile phones to call for an emergency. Social services in the Czech Republic provide support to individuals in managing specific situations. However, it does not resolve the financial crisis or the health issues of vulnerable patients. Some knowledge should be spread to this group to reduce risks. It can lead to a better understanding of one’s health and access to healthcare when needed.

Dostęp do opieki zdrowotnej jest obecnie bardzo powszechny. Osoby zdrowe zazwyczaj nie przywiązują wagi do sposobu dostępu do placówek opieki zdrowotnej. Jednak najczęstszym klientem placówki opieki zdrowotnej nie jest osoba zdrowa, lecz cierpiąca. W takim przypadku wiele ograniczeń może wpływać na dostęp do odpowiedniej opieki. Głównym celem badania była identyfikacja wszystkich potencjalnych barier ekonomicznych, które utrudniają dostęp do placówek opieki zdrowotnej. Stworzyliśmy podstawy teoretyczne, wykorzystując metodę PRISMA-PICOT, a następnie skupiliśmy się na podejściu jakościowym, wykorzystując wywiady półustrukturyzowane do weryfikacji naszych teorii. Wyniki pokazują, że różne grupy osób funkcjonujące się w odmiennych uwarunkowaniach są podatne na zagrożenia. W zależności od podatności danej grupy i jej specyficznych potrzeb, istnieją różne bariery ekonomiczne, od niskich dochodów po niewystarczające możliwości podróżowania. Na przykład osoby z obszarów wiejskich często mają ograniczone możliwości transportu, a wiele z nich nie jest w stanie skorzystać z telefonu komórkowego, aby wezwać pomoc w nagłych wypadkach. Służby socjalne w Czechach zapewniają wsparcie osobom w radzeniu sobie z konkretnymi sytuacjami. Nie rozwiązuje to jednak kryzysu finansowego ani problemów zdrowotnych pacjentów w trudnej sytuacji. Żeby zredukować ryzyka występujące wśród tej grupy osób należy edukować i upowszechniać wiedzę. Może to prowadzić do lepszego zrozumienia własnego zdrowia i dostępu do opieki zdrowotnej, gdy jest ona potrzebna.
Bariery ekonomiczne i ich wpływ na dostęp do usług ochrony zdrowia
Keywords: barriers; healthcare; needs; vulnerability; people; bariery; opieka zdrowotna; potrzeby; podatność; ludzie